Compósitos anfifílicos magnéticos contendo ferro e carbono : Síntese,caracterização e aplicações - Aline Almeida da Silva (2014)
Amphiphilic magnetic composites were prepared, characterized and used as catalytsts for biphasic reactions. Two distinct groups of composites were studied: (i) composites produced from synthetic matrixes, silica and nanoalumina and (ii) composites produced from Red mud (Rm), an industrial iron-rich waste. The composites were synthesized via CVD reaction (chemical vapor deposition) for Cdeposition on the surface of the matrixes. The amphiphilic character of the composites is consequence of the combination of a hydrophilic matrix and a partial hydrophobic carbon coating. The amphiphilic character arises from the reduced iron phases formed during CVD, i.e. Fe3O4, Fe0 and Fe3C. The synthetic matrixes were previously impregnated with metallic catalysts, Fe or Fe/Mo, while Rm was used in its pure form,due to its original iron content around 30%. On the synthesis of the composites with inert matrixes, methane was used as C source and the content of metallic catalysts was ranged: Fe (1 - 10%) and Mo (0.1 1%). For the Rm composites, two series of composites were prepared using different methodologies: (i) CVD reaction in fixed bed with ethanol as carbon source quenched at different temperatures and (ii) CVDreaction in fluidized bed with ethylene and/or acetonitrile as C and N sources. The composites were characterizes by several techniques: atomic absorption spectrometry, Mössbauer spectroscopy, X-ray diffraction, thermal analysis, elemental analysis, Raman spectroscopy, scanning electron microscopy, transmission electron microscopy, EDS microanalysis and porosity and specific surface area measurements. It was observed that the carbon source reduces the metallic phases on the matrix surface with the concomitant C deposition mainly as carbon nanotubes and nanofibers. The composites synthesized have shown to be efficient in the formation and break of emulsions and in the catalysis of biphasic oxidation reactions. The composites act on the interface intensification and in the decomposition of H2O2 in hydroxyl radicals (HO) by the action of Fe or Mo nuclei in a Fenton-like mechanism. The oxidation of sulfur and nitrogen organic contaminants was studied via the Fenton mechanism. The main contaminants tested were tiophene, dibenzothiophene and quinoline, compouds characteristic of petroleum containg S or N. Results showed that composites reached100% contaminants removal in the conditions studied. The composites produced with Rm and ethylene and/or acetonitrile presented high C content, which hindered the action of iron in the decomposition of H2O2. These composites were then applied in the adsorption of organic emergent contaminants, ethinylestradiol and bisphenol A withpromising eficiencies, reaching an adsorption capacity of 40 mg g-1.